2012
DOI: 10.1002/chem.201200159
|View full text |Cite
|
Sign up to set email alerts
|

Iron Borohydride Pincer Complexes for the Efficient Hydrogenation of Ketones under Mild, Base‐Free Conditions: Synthesis and Mechanistic Insight

Abstract: The new, structurally characterized hydrido carbonyl tetrahydridoborate iron pincer complex [(iPr-PNP)Fe(H)(CO)(η(1)-BH(4))] (1) catalyzes the base-free hydrogenation of ketones to their corresponding alcohols employing only 4.1 atm hydrogen pressure. Turnover numbers up to 1980 at complete conversion of ketone were reached with this system. Treatment of 1 with aniline (as a BH(3) scavenger) resulted in a mixture of trans-[(iPr-PNP)Fe(H)(2)(CO)] (4a) and cis-[(iPr-PNP)Fe(H)(2)(CO)] (4b). The dihydrido complexe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
176
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 185 publications
(182 citation statements)
references
References 101 publications
6
176
0
Order By: Relevance
“…[8] Milstein has reported pincerbased iron hydrogenation catalysts for symmetric reduction of ketones. [10,11 ] Morris and co-workers have applied chiral ironbased hydrogenation catalysts with tridentate [Fe(P-N-P)] and tetradentate [Fe(P−N−N−P) ligands in the asymmetric hydrogenation of ketones and imines. [ 12 , 13 ] Casey and Guan reported symmetric hydrogenation of aldehydes, ketones, and imines with Knölker's iron complex, which possesses a cyclopentadienone ligand.…”
Section: Introductionmentioning
confidence: 99%
“…[8] Milstein has reported pincerbased iron hydrogenation catalysts for symmetric reduction of ketones. [10,11 ] Morris and co-workers have applied chiral ironbased hydrogenation catalysts with tridentate [Fe(P-N-P)] and tetradentate [Fe(P−N−N−P) ligands in the asymmetric hydrogenation of ketones and imines. [ 12 , 13 ] Casey and Guan reported symmetric hydrogenation of aldehydes, ketones, and imines with Knölker's iron complex, which possesses a cyclopentadienone ligand.…”
Section: Introductionmentioning
confidence: 99%
“…in direct, efficient hydrogenation of CO 2 to methanol). The development of efficient catalysts based on iron pincer complexes is an important challenge; promising results in the hydrogenation of ketones and CO 2 were already obtained [23][24][25]. …”
Section: Resultsmentioning
confidence: 99%
“…While there are many examples of Ru-catalysed hydrogenations of ketones and aldehydes [7,11], and recently Fe-catalysed hydrogenation of ketones was also reported [35][36][37][38][39], including our system based on pincer-iron complexes [24,25], catalytic hydrogenation of esters, particularly non-activated ones, under mild conditions is a challenging task [6,7,9,10,40,41]. In pioneering work by Elsevier et al various aromatic and aliphatic esters were hydrogenated in fluorinated solvent using in situ prepared ruthenium complexes bearing P,P,P ligands at high pressure of dihydrogen under basic conditions [42].…”
Section: Hydrogenation Of Non-activated Esters To the Corresponding Amentioning
confidence: 97%
See 1 more Smart Citation
“…Copper(I) tetrahydroborates with phosphine ligands featuring relative stability to air oxygen and moisture are used as selective reducing agents [36][37][38][39][40], catalysts of photosensitized isomerization of dienes [41][42][43] and hydrolytic dehydrogenation of ammonia borane [44]. Since metal tetrahydroborates have great potential in hydrogen storage technology [45][46][47][48][49][50], as catalysts [51][52][53][54][55] and selective reducing agents [56][57][58][59][60][61] their structural and dynamic properties have been actively investigated [52,[62][63][64]. These studies revealed different modes of BH 4 − coordination to the metal atom, which can behave as mono-, bi-, or tridentate ligand [64].…”
Section: Introductionmentioning
confidence: 99%